2019
DOI: 10.1109/tasc.2018.2882426
|View full text |Cite
|
Sign up to set email alerts
|

Robust Design Optimization of a High-Temperature Superconducting Linear Synchronous Motor Based on Taguchi Method

Abstract: This paper investigates the efficient robust design and optimization of a high-temperature superconducting (HTS) linear synchronous motor by using the Taguchi parameter design approach. The manufacturing tolerances of the HTS magnets, primary iron core and the air gap are considered in the robust design to ensure that the optimal design is less sensitive to these uncertainties. To overcome the disadvantages of the conventional Taguchi parameter design approach, a sequential Taguchi robust optimization method i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 23 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…c) Cyber security consolidates the confidentiality, integrity, and availability of computing resources, networks, software programs, and data into a coherent collection of policies, technologies, processes, and techniques to prevent the occurrence of an attack (Berman et al, 2019). Cyber security refers to a combination of technologies, processes and operations that are framed to protect information systems, computers, devices, programs, data and networks from internal or external threats, harm, damage, attacks or unauthorized access for example ransom ware, denial of service attacks (Lei et al, 2019). The rapid advances in mobile computing, communications and mass storage architectures have precipitated the new phenomena of Big Data and Internet of Things (IoT).…”
Section: Technological Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…c) Cyber security consolidates the confidentiality, integrity, and availability of computing resources, networks, software programs, and data into a coherent collection of policies, technologies, processes, and techniques to prevent the occurrence of an attack (Berman et al, 2019). Cyber security refers to a combination of technologies, processes and operations that are framed to protect information systems, computers, devices, programs, data and networks from internal or external threats, harm, damage, attacks or unauthorized access for example ransom ware, denial of service attacks (Lei et al, 2019). The rapid advances in mobile computing, communications and mass storage architectures have precipitated the new phenomena of Big Data and Internet of Things (IoT).…”
Section: Technological Dynamicsmentioning
confidence: 99%
“…The rapid advances in mobile computing, communications and mass storage architectures have precipitated the new phenomena of Big Data and Internet of Things (IoT). Outsider and insider threats can have serious implications on an institution for example, failure to provide services, higher costs of operations, loss in revenue, and reputational damage (Gheyas and Abdullah, 2016;Lei et al, 2019). Therefore, an effective cyber security model must be able to mitigate cyber security events such as unauthorized access, zero day attack, denial of service, data breach, malware attacks, social engineering (or phishing), fraud and spam attacks, through intrusion detection and malware detection (Kantarcioglu and Xi, 2016;Sarker et al, 2020).…”
Section: Technological Dynamicsmentioning
confidence: 99%
“…A main driving force behind this is that robust design optimization is able to include the manufacturing data and product quality into the design problem. There are many research activities about the robust design analysis and optimization of different types of electromagnetic devices, such as SMES [21,[50][51][52][53], and several types of electrical machines including high-temperature superconducting linear synchronous motor [55], and synchronous reluctance motors [56], and PM motors [57][58][59][60][61][62][63][64][65]. It is observed that there are more discussions on robust design optimization of PM motors than other types of electrical machines, due to the fact that there are many uncertainties for the PMs.…”
Section: Design Optimization Models In the Presence Of Uncertaintiesmentioning
confidence: 99%
“…However, for robustness optimization, Taguchi's formulas, also in combination with other methods, still offer a great way to explore, visualize, and optimize the systems robustness by dividing the model's factors into decision and noise [38,41]. This is why they still today are the subject of current research [19,28], especially in the simulation community [12,22,44]. The strength of simulation-based robustness optimization using Taguchi's formulas is that a broad range of possible noise and decision configurations can be evaluated when large-scale experiment plans are used.…”
Section: Introductionmentioning
confidence: 99%